Exploring mental health awareness project, societal well-being and stigma among Tesol students: From multicultural awareness perspective - Akhter, Shamim; Kumar, Tribhuwan; Prasad, Rabindra Dev; Nukapangu, Venkanna (Research Journal in Advanced Humanities, 2025)
Mental illness misconceptions, preconceptions, stigma, and discrimination are important healthcare concerns that must be addressed to improve the well-being at the societal and individual levels. The stigma prevents people with mental health disorders from obtaining competent assistance. Based on self-determination theory (SDT), this paper attempts to uncover an association of mental health awareness (MHA) and mental health stigma (MHS) with societal well-being (SWB).  For performing an empirical investigation, the present research is assuming that mental health awareness (MHA) negatively affects mental health stigma (MHS). Moreover, this study also hypothesized that mental health stigma (MHS) is adversely associated with societal well-being (SWB). In addition, this research attempts to assess the mediating role played by the mental health stigma (MHS) in the relationship between mental health awareness (MHA) and societal well-being (SWB). Finally, the primary purpose of this research is to assess the moderating effect of multicultural awareness (MA) on the relationship between mental health awareness (MHA) and mental health stigma (MHS). For empirical investigation, the present study collected the data from 345 students who are enrolled in TESOL course offered in different degree awarding institutes in China. Furthermore, data was collected by using convenient sampling techniques. PLS-SEM was used in study to assess hypothesized relationships. The present research work acknowledged that mental health awareness (MHA) negatively relates to mental health stigma (MHS). Results of this study also confirmed that mental health stigma (MHS) negatively affects societal well-being (SWB). Moreover, the results of this study revealed that mental health stigma (MHS) does not negatively mediate the link between mental health awareness (MHA) and societal well-being (SWB). Further, the results authenticate that multicultural awareness (MA) positively moderates the link between mental health awareness (MHA) and mental health stigma (MHS). Findings of this research have necessary practical implications for improving the students’ mental health literacy and awareness.